Between Memorization and Critical-Transformative Pedagogy: Translating Islamic Religious Education Reform in Indonesia and Malaysia - Alwazir Abdusshomad; Benny Kurnianto; Nawang Kalbuana (J-PAI: Jurnal Pendidikan Agama Islam, 2026)
This article examines how official curriculum texts in Indonesia and Malaysia translate Islamic Religious Education (IRE) reform into pedagogical design. It addresses a curricular translation gap: reform vocabulary such as critical thinking, learner agency, religious moderation, ethical judgment, and digital discernment is increasingly visible in policy discourse, but its conversion into classroom-actionable pedagogy remains uneven. Using qualitative document analysis and reflexive thematic analysis, the study examines purposively selected official curriculum texts, teacher and student materials, Malaysian DSKP standards, and UNESCO reform frameworks published or accessed between 2021 and 2025. The documents were selected because they make visible learning outcomes, activity sequences, teacher guidance, assessment expectations, and transnational reform language relevant to IRE. The analysis distinguishes competency rhetoric from operational pedagogy by examining whether reform aims are supported by task sequences, teacher moves, student roles, and assessment criteria. Four findings are presented: memorization and correct performance remain the most procedurally explicit elements; criticality is often stated as an outcome rather than scaffolded as practice; moral formation is strongly visible but is not always accompanied by ethical reasoning routines; and transformative elements exist but are fragmented across curriculum components. The article contributes by conceptualizing the curricular translation gap and by proposing a staged curriculum logic in which memorization supports comprehension, interpretation, dialogue, ethical reasoning, and responsible action.